ANALISIS TIPOLOGI PESERTA DIDIK DARI SEGI EMOSIONAL DALAM PERSPEKTIF HADIS - Zakiah, Afidatuz (Ensiklopedia of Journal, 2025)
It is very important for educators to know the individual differences possessed by students in the learning process. In the teaching and learning process, various types of children will be encountered, there are talented children, less talented children, children who have high abilities, and vice versa. The Hadith of the Prophet SAW also explains the individual differences in the types of each student. The purpose of this study is to reveal the typology of students in terms of emotion in the Hadith. This study is a library research by modifying the thematic or maudhu'i approach, namely the analytical thematic approach. Data sources are in the form of hadith syarah books, educational books, journals related to research studies. The results of this study reveal that each student faced by educators has a different type according to the individual differences that each of them has brought. This is explained in the Hadith of the Prophet SAW. Regarding the typology of students in terms of differences in emotional levels, there are three types, namely patient students, namely students who are slow to get angry and quick to control themselves, impatient students, namely students who get angry quickly but can also quickly control it, and impatient students, namely students who get angry quickly and take a long time to control their anger.Keywords: Students, Emotional, Hadith